Comparative genomic reveals clonal heterogeneity in persistent staphylococcus aureus infection - Klein, Sabrina; Morath, Benedict; Weitz, Daniel; Schweizer, Patrick Alexander; Sähr, Aline; Heeg, Klaus; Boutin, Sébastien; Nurjadi, Dennis (Frontiers in Cellular and Infection Microbiology, 2022)
Persistent infections caused by Staphylococcus aureus remain a clinical challenge. Adaptational mechanisms of the pathogen influencing infection persistence, treatment success, and clinical outcome in these types of infections by S. aureus have not been fully elucidated so far. We applied a whole-genome sequencing approach on fifteen isolates retrieved from a persistent S. aureus infection to determine their genetic relatedness, virulome, and resistome. The analysis of the genomic data indicates that all isolates shared a common clonal origin but displayed a heterogenous composition of virulence factors and antimicrobial resistance. This heterogeneity was reflected by different mutations in the rpoB gene that were related to the phenotypic antimicrobial resistance towards rifampicin and different minimal inhibitory concentrations of oxacillin. In addition, one group of isolates had acquired the genes encoding for staphylokinase (sak) and staphylococcal complement inhibitor (scn), leading to the truncation of the hemolysin b (hlb) gene. These features are characteristic for temperate phages of S. aureus that carry genes of the immune evasion cluster and confer triple conversion by integration into the hlb gene. Modulation of immune evasion mechanisms was demonstrated by significant differences in biofilm formation capacity, while invasion and intracellular survival in neutrophils were not uniformly altered by the presence of the immune evasion cluster. Virulence factors carried by temperate phages of S. aureus may contribute to the course of infection at different stages and affect immune evasion and pathogen persistence. In conclusion, the application of comparative genomic demonstrated clonal heterogeneity in persistent S. aureus infection.
Gesehen am 11.05.2022